The seeds ebook - Nocenti, Ann (The Seeds., 2021)
The hotly-anticipated eco-fiction tech thriller-meets-love-story from the award-winning, visionary team of Ann Nocenti (Daredevil, Ruby Falls) and David Aja (Hawkeye, Immortal Iron Fist)!The bees are swarming. What do they know that we don't?In a broken-down world, a rebellious group of ruthless romantics have fled a tech-obsessed society to create their own...and a few cantankerous aliens have come to harvest the last seeds of humanity.When one of them falls in love with a human, idealistic journalist Astra stumbles into the story of a lifetime, only to realize that if she reports it, she'll destroy the last hope of a dying planet. How far will she go for the truth?Collects The Seeds #1-#4.""The perfect book for these deeply imperfect times."" -- Matt Fraction""Beautifully drawn, cleverly constructed and very satisfying."" -- Frank Quitely Author: Ann Nocenti. Illustrator: David Aja.